2021
DOI: 10.1021/jacs.1c04722
|View full text |Cite
|
Sign up to set email alerts
|

Decatungstate-Catalyzed C(sp3)–H Sulfinylation: Rapid Access to Diverse Organosulfur Functionality

Abstract: Here we report the direct conversion of strong, aliphatic C(sp 3 )−H bonds into the corresponding alkyl sulfinic acids via decatungstate photocatalysis. This transformation has been applied to a diverse range of C(sp 3 )-rich scaffolds, including natural products and approved pharmaceuticals, providing efficient access to complex sulfur-containing products. To demonstrate the broad potential of this methodology for the divergent synthesis of pharmaceutically relevant molecules, procedures for the diversificati… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

4
59
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 109 publications
(66 citation statements)
references
References 71 publications
(43 reference statements)
4
59
0
Order By: Relevance
“…Jiang and co-workers used sodium dithionite as the SO 2 source and reductant to generate alkyl sulfinates from activated esters in a sulfone synthesis, although no primary nonbenzylic substrates were included. Larionov has reported the synthesis of alkyl sulfonamides from carboxylic acids, and a recent report has shown that decatungstate photocatalysis can achieve C–H bond sulfination …”
mentioning
confidence: 99%
“…Jiang and co-workers used sodium dithionite as the SO 2 source and reductant to generate alkyl sulfinates from activated esters in a sulfone synthesis, although no primary nonbenzylic substrates were included. Larionov has reported the synthesis of alkyl sulfonamides from carboxylic acids, and a recent report has shown that decatungstate photocatalysis can achieve C–H bond sulfination …”
mentioning
confidence: 99%
“…144 A procedure for decatungstate photocatalyzed aliphatic C-H bond sulfinylation was developed very recently. 145 The proposed mechanism entails HAT from a substrate C-H bond to DT* ([W 10 O 32 ] 4À *) to give an intermediate carbon centered radical that is captured by SO 2 leading to the formation of a sulfonyl radical. Disproportionation of reduced decatungstate ([W 10 O 32 ] 5À ) generates [W 10 O 32 ] 6À that undergoes ET to the sulfonyl radical to afford the sulfinylated product (Scheme 137).…”
Section: Other Functionalizationsmentioning
confidence: 99%
“…Protonation of basic nitrogen centers is increasingly employed as a strategy to implement site-selectivity in HATbased aliphatic C-H bond functionalization procedures. 70,145,163 By inverting the polarity of the nitrogen functionality, strong electronic deactivation at proximal sites occurs enabling functionalization at remote and intrinsically less activated C-H bonds. 38 In the oxidation of abiraterone acetate and a g-secretase inhibitor analogues with hydrogen peroxide catalyzed by [Fe((R,R)-CF 3 pdp)], selective functionalization at the least electronically deactivated methylene site was observed in both cases following protonation by HBF 4 (structures VIII and IX).…”
Section: Other Functionalizationsmentioning
confidence: 99%
“…1Bc). 13 The Willis group reported that versatile alkyl sulfinates can be prepared from readily available amines, using Katritzky pyridinium salt intermediates by a photoinduced or thermally induced single-electron transfer (SET) process, and fluorination of alkyl sulfinates with NFSI can lead to the desired aliphatic sulfonyl fluorides as well (Fig. 1Bc).…”
Section: Introductionmentioning
confidence: 99%